Development of the mosquito pathogen Leptolegnia chapmanii (Straminipila: Peronosporomycetes) on an inexpensive culture medium based on sunflower seed. Issue 3 (3rd March 2016) - Rueda-Páramo, Manuel E.; Manfrino, Romina G.; Gutierrez, Alejandra; López-Lastra, Claudia C.; García, Juan J.
ABSTRACT: An inexpensive culture medium based on sunflower seed extract (SSE) for production of Leptolegnia chapmanii was developed. Vegetative growth on solid and liquid SSE was compared with two culture media used routinely (peptone, yeast and glucose (PYG) and Emerson YPss). Results indicate that the oomycete is able to grow on SSE medium, producing more zoospores at a faster rate as well as inducing higher mortality rates in Aedes aegypti larvae.